'For me at 90, it's going to be difficult': feasibility of using iPad video-conferencing with older adults in long-term aged care. (1st February 2020) - Moyle, Wendy; Jones, Cindy; Murfield, Jenny; Liu, Fangli
Abstract: Objectives: To explore the feasibility of using the video-conferencing program, Skype, on iPads with older adults living in long-term care (LTC) facilities. Method: Using a mixed-method design, six residents from one LTC facility in Queensland, Australia participated in a one-off interactive intervention session, followed by post-session semi-structured interviews. The intervention session involved a 15-minutes training session in using Skype, and 30-minutes interactive practise in making and receiving a call using Skype. Residents were interviewed after the intervention session to explore their experience and perceptions of using Skype on the iPad. Reflections about the intervention session were written as study notes by the research team. Qualitative data were analysed using an inductive, thematic analytic approach. Results: Four broad themes emerged: (1) Video-conferencing on iPads is inhibited by age-related cognitive decline and physical frailty; (2) Video-conferencing is an unfamiliar technology for many older residents, and practice and staff assistance are required; (3) Video-conferencing is regarded positively, and seen as a good way of communicating with family/friends; and (4) Use of video-conferencing highlights general concerns held about privacy and cyber security issues. Conclusion: Without adequate staff assistance, video-conferencing via iPads may be challenging for an older population in LTC. Alternatives such as telepresence robots may assist with these challenges.